ELECTRONIC EDUCATIONAL RESOURCES FOR TRAINING QUALIFIED WORKERS IN THE PROFESSION OF TURNERS (Innovative professional education, 2025)
The article examines the use of electronic educational resources in the training of skilled workers in the profession of turner. The main types of electronic resources are analyzed, including electronic textbooks, multimedia programs, virtual simulators, online courses, and professional communities. The key advantages of using digital technologies in the educational process have been identified, including accessibility, interactivity, personalization, and cost-effectiveness. The main challenges of implementing such resources are outlined and possible ways to overcome them are suggested. The use of modern electronic technologies contributes to increasing the level of knowledge and practical skills of future turners, which ensures their competitiveness in the labor market.
Keywords: Electronic learning resources, digital technologies, multimedia programs, virtual simulators, online courses, professional education